Urbanization and Related Environmental Issues of Metro Manila - Regmi, Ram Krishna (Journal of Advanced College of Engineering and Management, 2018)
Due to rapid urbanization, Metro Manila is facing many environmental challenges with its continuous accelerating urban growth rate. According to 2010 census of population Metro Manila accounts about one-third of the total urban population and about 13% of the total national population of Philippines. The impact of urban growth of the Metro Manila to its urban environment relating on demography, solid wastes problem and problems in water bodies as well as air pollution and greenhouse gas emissionis emphasized here in this study. The flood prone areas within the Metro Manila is about 31%, most of the risk areas located along creeks, river banks or coastal areas. Metro Manila produces total garbage equivalent to 25% of the national waste generation in which about 17% is paper wastes and about 16% are plastics. In terms of water quality classification the upper reaches of the Marikina River is of Class A, but all remaining river systems are of Class C. Accordingly, the classification of Manila Bay is of Class SB. Similarly, the quality of ambient air of the Metro Manila is also poor. Using 2010 as base year, the major contributor to greenhouse gas is from vehicular emissions followed by the stationary sources. An urgent need is felt to incorporate environmental issues into planning its urban area to reduce the risks of further environmental degradation. Journal of Advanced College of Engineering and Management, Vol. 3, 2017, Page: 79-92